Strategi Coping Istri Dari Suami Penjudi Dalam Mempertahankan Keutuhan Keluarga - anggi Friscilia; Wanda Fitri; Masrial; Elvina, Siska Novra; Ilmiyati Refi Fadia (Universitas Islam Ahmad Dahlan, 2024)
This research is motivated by the assumption that the wife whose husband likes to gamble experiences psychological and social pressure, so that the wife can experience a stressful situation in dealing with these problems. Ideally, the image of a wife who has been harmed physically and mentally or psychologically and socially usually has a household condition that is not harmonious or has conflicts. But in reality there are still wives who persist in husband and wife relationships even though they have been persecuted psychologically and socially. The method used in this research is qualitative with a descriptive approach. Data collection techniques using observation and interviews. The research subjects are the wives of gamblers who live in Kanagarian Muara Kandis Punggusan, Pesisir Selatan, totaling 6 people, the technique of determining the subject is using a purposive sampling technique with certain criteria. The results showed that in the aspect of problem focused coping, generally the wife has a strong stance to maintain the integrity of her family. Then in the aspect of emotional focused coping, the majority of wives are able to control themselves but there are also those who vent to negative behavior such as smoking and to prevent fighting, the majority of informants choose to avoid their husbands and no one leaves the house or leaves. husband and children.